2019
DOI: 10.1002/bjs.11146
|View full text |Cite|
|
Sign up to set email alerts
|

Association between surgeon special interest and mortality after emergency laparotomy

Abstract: on behalf of the NELA Collaboration Br J Surg 2019; 106: 940-948.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 24 publications
(23 reference statements)
1
35
0
Order By: Relevance
“…Whilst outcomes have improved over time, ongoing research continues to highlight potential contributing factors that may affect the morbidity and mortality observed following emergency surgery. Ideas such as the ‘weekend effect’ [6], the effects of frailty [7] and the impact of subspecialization have all been studied within general surgery [8,11,31]. Of the 24 328 patients assessed in the latest NELA report, colorectal emergency resections accounted for three of the five most commonly performed procedures [5].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst outcomes have improved over time, ongoing research continues to highlight potential contributing factors that may affect the morbidity and mortality observed following emergency surgery. Ideas such as the ‘weekend effect’ [6], the effects of frailty [7] and the impact of subspecialization have all been studied within general surgery [8,11,31]. Of the 24 328 patients assessed in the latest NELA report, colorectal emergency resections accounted for three of the five most commonly performed procedures [5].…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the study by Boyd et al . which found an increase in mortality in colorectal and upper gastrointestinal (GI) emergency laparotomy performed by non‐specialist surgeons.…”
mentioning
confidence: 99%
“…We aim to conduct future research in our unit to see if the findings of this study are applicable to local setting.…”
mentioning
confidence: 99%
“…Ramsay et al's study on the reduction of mortality after surgery in Scotland continued to stimulate debate about the role that the WHO checklist played in this effect 5 . Boyd-Carson et al's study on the association between surgeon special interest and mortality after emergency laparotomy continued to have a high impact on Twitter 6 . @kmahawar commented that when non-gastrointestinal (GI) surgeons were removed from the analysis, there was no increased risk of return to theatre for either upper GI or colorectal procedures, and suggested that this was because patients died of non-surgical complications.…”
mentioning
confidence: 99%